RETRATOS DE UMA DOENÇA: ESTUDO DAS IMAGENS DA EPIDEMIA DE ZIKA A PARTIR DOS PERFIS DE MÍDIA NO TWITTER - Honorato, Johanna Inacia (2020)
This work aims to understand how the images that circulated during the Zika Virus epidemic in the media profiles within the social network Twitter built a narrative of the disease with its own characteristics. To this end, 6 million publications were coll